The Oxford handbook of entrepreneurial finance - Cumming, Douglas (New York ; Oxford : Oxford University Press, 2012)
The topic of entrepreneurial finance involves many issues including but not limited to the risks and returns to being an entrepreneur, financial contracting, business planning, capital gaps and the availability of capital, and market booms and busts. This handbook provides a comprehensive picture of these issues.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Small business -- Finance; Entrepreneurship